Hubungan Kausalitas Antara Ketimpangan Pendapatan, Pertumbuhan Ekonomi, dan Kemiskinan di Indonesia - Dicky Fernando; Syamsul Amar (Universitas Negeri Padang, 2021)
This study aims to explain the causality relationship between income inequality, economic growth, and poverty in Indonesia. In this study using a panel regression model. And data used are time series data from 2011-2017, Consisting of 32 provinces. This data is obtained from BPS annual report. The result of this study indicate that (1) There is no causal relationship between economic growth and poverty (2) There is a causal relationship between income inequality and poverty (3) There is a one-way causal relationship between economic growth and income inequality.